Manajemen Ekstrakurikuler di Madrasah Ibtidaiyah sebagai Wahana Mendidik Karakter Peserta Didik - Erra Sanianingtyas; Burhanuddin Burhanuddin; Imron Arifin (Universitas Negeri Malang, 2023)
Abstract: Writing this article aims to find out how the extracurricular management process starts from planning, organizing, implementing, and supervising as a vehicle for educating the character of students at MI Manarul Islam and MI Khadijah Malang City. This article uses a qualitative approach with a multi-site study type of research. Data collection techniques through in-depth interviews, observation, and documentation. The informants in this study were school principals, student assistants, extracurricular coordinators, and extracurricular coaches. The results of this study indicate that the extracurricular management process in Madrasah Ibtidaiyah supports the development of the character of students, namely cooperation, religion, tolerance, mutual assistance, integrity, respect for differences, sportsmanship, maintaining cleanliness, training leadership, discipline, independence, self-confidence, responsibility, obedience , never give up, work hard, concentrate and focus, these characters will affect learning at school and outside of school.Keywords: management; extracurricular; student characterAbstrak: Penulisan artikel ini bertujuan untuk mengetahui bagaimana proses manajemen ekstrakurikuler mulai dari perencanaan, pengorganisasian, pelaksanaan, dan pengawasan sebagai wahana mendidik karakter peserta didik di MI Manarul Islam dan MI khadijah Kota Malang. Artikel ini menggunakan pendekatan kualitatif dengan jenis penelitian studi multi situs. Teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Informan dalam penelitian ini yaitu kepala sekolah, waka kesiswaan, koordinator ekstrakurikuler, dan pembina ekstrakurikuler. Hasil penelitian ini menunjukkan bahwa proses manajemen ekstrakurikuler di Madrasah Ibtidaiyah menunjang pengembangan karakter peserta didik yaitu bekerja sama, religius, bertoleransi, saling membantu, integritas, menghormati perbedaan, sportifitas, menjaga kebersihan, melatih kepemimpinan, disiplin, mandiri, percaya diri, bertanggungjawab, ketaatan, pantang menyerah, bekerja keras, berkonsentrasi dan fokus, karakter tersebut akan berpengaruh terhadap pembelajaran di sekolah maupun di luar sekolah.Kata kunci: manajemen; ekstrakurikuler; karakter peserta didik